Pengaruh Faktor Perpajakan terhadap Kepatuhan Membayar Pajak Kendaraan Bermotor dengan Kesadaran sebagai Variabel Moderasi : Studi pada Kantor Samsat Kabupaten Nganjuk - Elfina Elfina; Puji Astuti; Sugeng Sugeng (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research is motivated by the fluctuation in the level of motor vehicle taxpayer compliance in Nganjuk Regency, which raises the need to evaluate the factors that influence it. Tax knowledge, quality of tax services, and service modernization through the e-Samsat system are considered important variables in improving compliance. In addition, taxpayer awareness is expected to strengthen the influence of these variables. The main objective of this study is to analyze the influence of tax knowledge, service quality, and e-Samsat system modernization on taxpayer compliance, by placing taxpayer awareness as a moderating variable. This study uses a quantitative approach with a causal-comparative research type. Data collection was carried out by distributing questionnaires to 100 respondents selected using a purposive sampling technique. The data analysis method used is Moderated Regression Analysis (MRA) with the help of SPSS software version 27. The results of the study indicate that tax knowledge has a significant influence on taxpayer compliance. In contrast, the quality of tax services and e-Samsat modernization do not have a significant influence on compliance. Furthermore, taxpayer awareness was shown to significantly moderate the relationship between tax knowledge and compliance, but did not act as a moderator in the relationship between service quality or e-Samsat system modernization and taxpayer compliance. This finding indicates that increasing taxpayer awareness can strengthen the effectiveness of tax education. However, administrative and digital approaches cannot optimally increase compliance without being accompanied by stronger awareness among taxpayers themselves.